INVITRO PROPAGATIONS AND MICRO RHIZOME INDUCTION OF ZINGIBERACEAE OFFICINALE - ALI, H; HUSSAIN, I; ALI, K; ALI, S; ALI, GM (Biological and Clinical Sciences Research Journal, 2024)
Ginger (Zingiber officinale Rosc.), is a rhizomatous crop that belongs to the Zingiberaceae family. Its bioactive ingredient has gained much attention for its many uses in medicine, food, and industry. Traditional rhizome propagation fails because of disease susceptibility, limited multiplication rates, and seasonal limitations. In vitro micropropagation and micro-rhizome induction may provide disease-free, genetically uniform plants throughout the year. Ginger micropropagation encounters contamination, soma clonal variance, hyperhydricity, Subculturing, and rigorous sterilizations. To mitigate these issues this review evaluates ginger micropropagation and in vitro micro-rhizome formation techniques. Ginger tissue culture requires explant selection and sterilization. Shoot tips, lateral buds, and rhizome segments exhibit variable responses to media compositions and sterilization methods. The fundamental medium is the Murashige and Skoog (MS) medium, which comprises organic compounds and carbon sources. The cytokine 6-benzylaminopurine influences shoot induction and proliferation. Reduced levels of NAA or IAA enhance shoot elongation and quality. To stop hyperhydricity and callus formation, which slow down shoot growth and regeneration, the right amounts of cytokinin and auxin must be present. The multiplication and storage of ginger depend on the production of micro-rhizomes, which requires certain concentrations of growth regulators and suitable environmental conditions. Rhizome development needs 6–8% sugar as an osmotic agent and energy source. Cytokinins and auxins, such as NAA and IBA, enhance micro-rhizome biomass. Photoperiod and temperature influence micro-rhizome development, with 16 hours of light and temperatures of 25 ± 2°C promoting growth. Plantlets must acclimate to soilless or substrate medium after in vitro cultivation. The micropropagation of ginger and the induction of micro-rhizomes may enhance industrial output. This review aims to address the knowledge gap on the micropropagation of ginger by synthesizing and critically evaluating previous studies. It functions as a comprehensive resource for researchers and those aiming to improve ginger farming using sophisticated biotechnology methods.